Blade Weapons of Altai Population in Rouran Period (by the materials of the Choburak-I complex) - Seregin Nikolai N.; Tishkin Aleksey A.; Matrenin Sergey S.; Parshikova Tatyana S. (Поволжская археология, 2024)
The article presents the study of the collection of bladed weapons, obtained during the excavations of the Rouran period burials on Choburak-I necropolis. This site is located in the Chemal district of the Altai Republic. The analyzed series of weapons includes three swords and six combat knives found in the burials of four adult men and one teenager. It has been established that the complex of long-bladed weapons is represented by single-edged blades without crosshairs and pommel, with a semi-segmental tip. The surviving combat knives with a triangular blade section are divided into two types, distinguished by a straight handle and a handle inclined towards the blade. The published collection demonstrates typical examples of weapons of the nomads of Central Asia of the 4th – 5th centuries AD. New excavation materials confirm the thesis that swords were a status category of weapons among the population of Altai during the Great Migration period. Burials with such items, investigated as part of the Choburak-I necropolis, differed in the representative composition of the inventory, and, judging by the available data, belonged to military leaders or especially distinguished professional soldiers.